Intellectual role performance in leading English newspapers in Mainland China: A CDA perspective - Yin, Kexiu (Animo Repository, 2014)
The academic interest in the notion of intellectuals and intellectual roles has lasted over a century since intellectuals became confirmed as a new political phenomenon in the Dreyfus Affairs. Making the disclosure of public events is a way of performing the intellectual roles. However, few discourse analysts have focused on the intellectual role performance. With the theoretical and methodological insights from the critical discourse analysis (CDA), the study aims to explore how the intellectual role performance can be systematically examines and discussed by discourse analysts. The context of the study is located in mainland China, and the purpose is to examine whether the intellectual roles have been duly performed in the discourse of the five selected public events across 2008-2012 in the leading English newspapers in mainland China. Three corpora for each event are built, altogether consisting of 254 texts taken from the leading English newspapers in Hong Kong and 83 texts from other international English newspapers. The intellectual discourse of mainland China in the study refers to the discourse in the 254 texts. Through the comparison of the texts from the three sources, the texts of the latter two sources facilitate the description and interpretation of the intellectual discourse properties. In order to investigate the intellectual role performance in terms of speaking the truth, speaking with the critical spirit and speaking for the public, the discourse properties are identified in the inclusivity of topics, the inclusivity of topics, the inclusivity of competing views on selected topics and themes in the macrostructure. Based on the findings of the intellectual discourse, the role performance is discussed in three aspects. First, the low inclusivity of topics in general presents the possibility of missing a considerable amount of information on the public events, which indicates that the role performance in terms of speaking the truth may be compromised. Second, the overall low inclusivity of competing views on selected topics reflects a lack openness to different opinions of the public events, which shows that the role of speaking with the critical spirit is not duly performed. Third, the general low frequency of themes referring to the public in the macrostructure especially in the conceptual categories of Headline, Lead and Verbal Reaction implies a less pro-public perspective in the discourse, which suggests that the role performance in terms of speaking for the public is unsatisfactory. After the discussion about the intellectual role performance, the possible social constraints on the performance are explored. It is inferred that the intellectual role performance, the possible social constraints on the performance are explored. It is inferred that the intellectual role performance may be affected by the state-owned background of the media, the reliance on advertising revenue, the dependence on government sourcing, the apprehension of flack and the fear of subversive forces. Finally, the implications for research on intellectual discourse are provided.